Fish-Bombing Fishermen From Barang Lompo Island, South Sulawesi Province: Understanding Their Corruption, Behaviors and Arranging Policy For Destructive Fishing Reduction - Andy Ahmad Zaelany (Journal of Indonesian Social Sciences and Humanities, 2019)
At present, corruption in the fishing sector has become a severe threat to the effectiveness of marine resource management. However, corruption activities that occur in fishing communities are still rarely revealed to the public due to the complexity and lack of researchers who are interested in learning them. The research aims to understand the behavior of the fish-bomb fishermen in Barang Lompo Island, South Sulawesi, in order to arrange suitable policy and program choice for reducing of using fish bombs in fishing activity. This research is conducted by a qualitative approach and ethnography method (participation observation) as well in a time series since 1999. The result showed that the corruption behaviors among the Barang Lompo fishermen are caused by several factors, i.e., aggressive culture, poverty, cultural burden and cultural pride, and consumerism. Corruption, in this case, makes a fishing business more efficient, with short working time indicators, and catches a lot.